Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/tbed.12841
|View full text |Cite
|
Sign up to set email alerts
|

Full-length genome sequence analysis of an avian leukosis virus subgroup J (ALV-J) as contaminant in live poultry vaccine: The commercial live vaccines might be a potential route for ALV-J transmission

Abstract: One avian leukosis virus subgroup J (ALV-J) strain was isolated from 67 commercial live poultry vaccines produced by various manufacturers during 2013-2016 in China. The complete genomes of the isolate were sequenced and it was found that the genes gag and pol of the strain were relatively conservative, while the gp85 gene of the strain GX14YYA1 had the highest similarities with a field strain GX14ZS14, which was isolated from the chickens of a farm that had once used the same vaccine as the one found to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The mutations of the new isolated ALV‐J strains, occurring in conserved regions, may be one of the factors for more severe oncogenicity. Besides mutation of virus, it also has other contributing reasons for the outbreak of avian leukosis, such as the vaccination of ALV‐contaminated live vaccines (Wang et al., ). Thus, the biocharacteristics, pathogenesis and novel control measures of ALV‐J should be further studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations of the new isolated ALV‐J strains, occurring in conserved regions, may be one of the factors for more severe oncogenicity. Besides mutation of virus, it also has other contributing reasons for the outbreak of avian leukosis, such as the vaccination of ALV‐contaminated live vaccines (Wang et al., ). Thus, the biocharacteristics, pathogenesis and novel control measures of ALV‐J should be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…Values along the branches indicate bootstrap values. The marker denotes a measurement of the relative phylogenetic distance [Colour figure can be viewed at wileyonlinelibrary.com] reasons for the outbreak of avian leukosis, such as the vaccination of ALV-contaminated live vaccines (Wang et al, 2018). Thus, the biocharacteristics, pathogenesis and novel control measures of ALV-J should be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…ALVs can be transmitted vertically or horizontally (Lin et al, 2013) and the commercial live vaccine might also be a potential route for ALVs transmission (Wang et al, 2018a). In this study, a strain that isolated from gamecocks was found to cause severe immunosuppression and tumor incidence in the commercial Three-Yellow chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Avian leukosis viruses ( ALVs ) are known as a variety of infectious retroviral agents that cause severe economic loss to the poultry industry worldwide (Payne and Nair, 2012). Avian leukosis viruses that infect chickens comprise 7 envelope subgroups designated A to E, J and K (Wang et al, 2018a). Subgroups A, B, C, D, J, and K are exogenous ALVs while subgroup E is endogenous (Su et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Avian leukosis virus belongs to the genus Alpharetroviru s and the family Retroviridae ( Wang et al., 2019 ). The proviral DNA arrangement of the genome of ALV was 5′LTR-leader- gag - pol - env -3′LTR and the full-length of the genome sequences of ALV was 7,200 bp-7,800 bp ( Wang et al., 2018a ). The LTR is the nonstructural gene, whereas gag , pol, and env are the structural genes ( Meng et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%